Nomenclatural notes on some autumn flowering daffodils (Narcissus, Amaryllidaceae) - Koopowitz, Harold; Howe, Marilynn; Christenhusz, Maarten J. M. (Phytotaxa, 2017)
Autumn flowering daffodils have been recorded in taxonomic history for at least 500 years. First descriptions were often merely based on hearsay, as they were often not studied alive. Consequently, many errors in interpretation of these names have occurred and taxonomic confusion, errors in identification and misapplication of names have led to an accumulation of taxonomic entanglement in Narcissus Linnaeus (1753: 289) nomenclature. In this paper we address some of these past confusions and provide a key to identify autumn flowering species.